Selecting Supplier with Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS): A Case Study at PT. Perta Daya Gas Semarang - Dwi Nurma Heitasari; Tri Warcono Adi (The Eastasouth Management and Business, 2023)
Supplier is an important part of the supply chain. The appropriate supplier would maintain the company's competitive advantage, and multi-criteria decision-making is applied in selecting suppliers. PT. Perta Daya Gas is a company that provides infrastructure and storage services for compressed natural gas. Machines are needed for operational activities that need components; one is the exhaust manifold. There are some considerations in selecting an exhaust manifold supplier, such as quality, delivery, price, and company conditions. Selecting suppliers use the Analytical Hierarchy Process (AHP) method for weighting, then continue to rank suppliers using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. Based on the AHP method, quality has the highest weight of 54.9%, and the highest weight on sub-criteria is the specification, 38.2%. Based on the TOPSIS method, PT. A has the highest preference value of 0.712. It shows that PT A is the best supplier, which could be prioritized in fulfilling the supply exhaust manifold in PT Perta Daya Gas